Maternal nutritional imbalance during pregnancy and the development of fetal-origin cardiovascular diseases - Cui, Shihua; Deng, Fengying; Lu, Muxue; Zhang, Meihua; Yang, Zedong; Ma, Yuchen; Fan, Linlin; Gao, Qinqin; Feng, Dairong (Frontiers in Nutrition, 2026)
The prenatal period is a critical window for cardiovascular development in offspring. Accumulating evidence demonstrates that maternal nutritional imbalances during pregnancy—encompassing undernutrition, overnutrition, and specific nutrient deficiencies—elicit adverse adaptations in fetal vascular systems, thereby predisposing offspring to cardiovascular disease (CVD) in later life. This review synthesizes current knowledge on the impact of macronutrient (e.g., high-sugar, high-fat diets) and micronutrient (e.g., vitamin D, folate) imbalances, as well as exposures to alcohol and caffeine, on offspring cardiovascular health. Key mechanisms such as epigenetic regulation (e.g., DNA methylation, histone modifications), oxidative stress, and endothelial dysfunction are discussed. Furthermore, we highlight future research directions and potential early nutritional interventions aimed at mitigating long-term cardiovascular risks and breaking the cycle of intergenerational metabolic disease. By integrating mechanistic insights and epidemiological evidence, this review underscores the importance of optimizing maternal nutrition as a pivotal public health strategy for preventing offspring CVD.